Gallium arsenide-based traveling wave electro-optic modulators - Cui, Yansong (University of Ottawa (Canada), 2004)
This thesis addresses research on the design and modeling of GaAs traveling wave electro-optic modulators with a highly doped layer. These modulators are in the form of a waveguide integrated with Planar Microstrip electrodes (PMS), and of a Mach-Zehnder interferometer integrated with capacitively loaded Coplanar Strips (CPS) electrodes. In both, the use of a thin highly doped layer ensures a good overlap between the applied electric field and optical mode. The design space of both PMS and loaded CPS electrodes are fully characterized. Waveguides of low propagation loss are designed. Wide bandwidth traveling wave modulators require low optical and microwave insertion loss, impedance matching, velocity matching and low half wave voltage. The simulation results predict that modulators with PMS electrodes have a limited frequency response while the modulators with CPS loaded electrodes have an electrical 3 dB bandwidth up to 70 GHz for 1cm device and Vpi of 9.4 V·cm.
Keywords: Engineering, Electronics and Electrical.; Engineering, Materials Science.